PENGARUH MATRICONDITIONING TERHADAP VIABILITAS DAN VIGOR BENIH KEDELAI YANG DISIMPAN DI RUANG TERBUKA - Youlanda M. Udi; Stanley A. F. Walingkas; Adeleyda M.W. Lumingkewas (COCOS, 2020)
ABSTRACKThis study aims to study the effect of matriconditioning on the viability and vigor of soybeanseeds stored in open spaces and to obtain the best type of media for the invigoration of soybean seeds,carried out in the new city sario sario in manado, for 3 (three) months from preparation to the completionof the research, namely in May to August 2020. The method used was a descriptive method, with 4 (four)treatments that were repeated 4 (four) times consisting of P1 (husk ash matriconditioning), P2 (red brickmatriconditioning that had been crushed), P3 (rubbing ash matriconditioning), P4 (fine sandmatriconditioning). The results showed that the matriconditioning treatment could increase the viability ofsoybean seeds in the parameters of germination, germination speed, sprouting height and root length. Ofall the matriconditioning treatments, the best material to increase the viability of soybean seeds is thematriconditioning treatment using mashed red bricks with a germination percentage of 84%, germinationspeed 16.8% / etmal, sprouting height of 7.5 cm and root length of 6 , 8 cm.Keywords: Soybean seed, Matriconditioning, Viability, Vigor